Values versus Interests Dynamics of Parliamentary Campaigns - Rafałowski, Wojciech (Political Preferences, 2018)
The paper explores the dynamics of parliamentary campaigns in Europe. Results obtained in the fields of pharmacology and psychology indicate that the emotional tension among the electorate rises as the election day draws closer. Therefore, parties should adjust their campaigning strategies accordingly. I am attempting to verify whether these dynamics influence the proportion between interest and value-related appeals within party communication. Using newly collected data from the Comparative Campaign Dynamics Project, I demonstrate that there is no general tendency towards the increasing saliency of either of the dimensions. However, the relationship under scrutiny becomes strong and robust after the moderating effects of inequality have been accounted for. Most strikingly, as the election draws closer, parties tend to focus more attention on economic issues only if the country experiences high or rising rates of inequality. Key words: party strategy, electoral campaign, campaign dynamics, emotions in politics, inequality